Exome-based cancer predisposition gene testing can provide a genetic diagnosis for individuals with heterogeneous tumor phenotypes - Hinić, Snežana; Mensenkamp, Arjen R.; Schuurs-Hoeijmakers, Janneke H. M.; Brugnoletti, Fulvia; Vreede, Lilian; van Veen, Elke M.; Mijzen, Barend; van der Post, Rachel S.; Genuardi, Maurizio; Ligtenberg, Marjolijn J. L.; Hoogerbrugge, Nicoline; de Voer, Richarda M. (European journal of human genetics : EJHG, 2025)
The development of multiple primary tumors is one of the hallmarks of hereditary cancer. The phenotypic presentation of individuals with multiple primary tumors is often heterogeneous, which hampers the establishment of a genetic diagnosis. The absence of a genetic diagnosis may lead to inappropriate surveillance advices and treatment choices. The aim of this study was to investigate whether whole-exome sequencing (WES) and variant prioritization in all genes associated with cancer predisposition can identify pathogenic variants that explain the phenotypes of individuals who developed multiple primary tumors. Here, we report the findings of exome-based cancer predisposition gene testing in individuals ( n = 72) who presented with multiple primary tumors (both malignant and benign) before the age of 65 years. Overall, a germline pathogenic variant (gPV) in a cancer predisposing gene was identified in 9.7% of individuals ( CHEK2 , FANCM , NF1 , POT1 and PTEN ) and a candidate variant in 4.2% of individuals ( HOXB13 , MAX and RECQL4 ). Furthermore, by analyzing variants that occur in genes in cancer-associated pathways, we identified a candidate gene ( RECQL5 ) for further follow-up. In conclusion, our study indicates that exome-based cancer predisposition gene testing may aid in the identification of pathogenic variants in individuals who developed multiple primary tumors. Our findings demonstrate that individuals with gPVs in genes associated with cancer predisposition may present with a broad tumor spectrum.